(untitled) (Research, Society and Development, 2019)
Throughout history the presence of women in some areas of knowledge has been questioned, censored or forgotten. In this study, we discuss the role of women in mathematics. The objective is to analyze the perception of undergraduate female students of mathematics course on female participation in mathematics. In this research we used a qualitative approach and the data were obtained through audio recording during a lesson, which at first used the methodology of an inverted classroom and in the second moment different materials. The results show, a priori, that in the participants’ perception there is a discomfort of the female gender in acting in the field of mathematics, for reporting there are still many challenges to be overcome in this area.